NILAI-NILAI ESTETIK SENI TRADISI TARI TERBANG TUMBAL - Gandara, Indra (2016)
Seni tradisi Tari Terbang Tumbal ini perlu untuk dilestarikan oleh masyarakat pendukungnya, karena dalam karya seni tradisi Tari Terbang Tumbal ini selain menyimpan banyak nilai estetik didalamnya, seni tradisi Tari Terbang Tumbal ini mengajarkan banyak hal mengenai pola hidup baik secara sosial, budaya dan lingkungan. Oleh sebab itu melalui penelitian ini peneliti ingin mengetahui lebih lanjut mengenai seni tradisi Tari Terbang Tumbal. Permasalahan yang terdapat dalam penelitian ini adalah sebagai berikut; 1) Bagaimana bentuk perwujudan seni tradisi Tari Terbang Tumbal ? 2) Bagaimana cara menilai isi secara pemahaman estetik yang terkandung pada seni tradisi Tari Terbang Tumbal ? 3) Apa saja makna dan simbol secara estetik yang terkandung dalam seni tradisi Tari Terbang Tumbal?. Penelitian ini menggunakan metode deskriptif kualitatif, karena metode deskriptif kualitatif, membantu peneliti dalam menggambarkan dan menguraikan nilai-nilai estetik dalam seni tradisi Tari Terbang Tumbal. Pendekatan triangulasi dipilih oleh peneliti, karena pendekatan ini membantu peneliti dalam menuangkan hasil analisis melalui kalimat atau kata-kata dari hasil observasi lapangan. Adapun hasil penelitian peneliti yaitu, dapat mengkategorikan pengkajian estetika dalam karya seni tradisi Tari Terbang Tumbal menjadi tiga kategori, sebagai berikut; a) wujud yang dinyatakan melaui stuktur penyajian pergelaran/pertunjukan seni tradisi Tari Terbang Tumbal, b) Bobot atu Isi dinyatakan dari peralihan fungsi sesanjen, c) Penyajian dinyatakan melalui pengalaman transendnsi (kasurupan lelembut karuhun), baik pada penari pembuka dan penari interaksi (penonton). Kata kunci: tari terbang tumbal, kajian nilai estetik, metode deskriptif kualitatif As well as the traditional arts Dance Terbang Tumbal , which does not loose its association with the expression of human feelings and attitudes involved in it , this impression would appear to be the realist , is formed to the surface from a depth of flavor into a synergy of beauty that is balanced in a more holistic view . Thus the authors chose art Tradition Dance Terbang Tumbal this , because according to the authors of traditional arts Dance Terbang Tumbal this needs to be preserved by the community of supporters , because of the work of art traditions of dance Fly Tumbal besides save a lot of aesthetic value in it , the traditional arts Dance Terbang Tumbal this taught me many things about life pattern whether social, cultural and environmental. Therefore, through this study, researchers wanted to find out more about the art of dance traditions Terbang Tumbal . Problems found in this study are as follows ; 1 ) How is the embodiment of the traditional art form Terbang Tumbal Dance ? 2 ) How do I rate the content contained on the aesthetic understanding of the art of dance traditions Terbang Tumbal Dance ? 3) What are the meaning and aesthetic symbols contained in art tradition Terbang Tumbal Dance ? This study uses qualitative descriptive method , because the descriptive qualitative methods help researchers in describing and outlining the aesthetic values in art tradition Terbang Tumbal Dance . Triangulation approach chosen by the researchers , because this approach helps researchers in the pouring analysis results through sentences or words from the results of field observations. The research results of researchers is, it can categorize assessment aesthetic in works of art tradition Dance Terbang Tumbal into three categories , as follows ; a ) the nature expressed through the structure of the presentation of the performance / performing arts traditions Dance Terbang Tumbal , b ) Weight atu Fill otherwise of conversion for sesajen , c ) Presentation is expressed through the experience transendnsi ( kasurupan lelembut ancestor ) , both on dancer opener and dancer interaction ( audience ) . Keywords : fly sacrificial dance , aesthetic value study , qualitative descriptive method